A case of cocaine trafficking via body packer as reported by chemical examiner laboratory, Punjab, India - Kaur, Kamaljit; Bansal, Abhey; Gupta, Rakesh; Singh, Harkirat (Journal of Indian Academy of Forensic Medicine, 2019)
Drug trafficking is a global illicit trade. The international drug trade uses various methods to smuggle narcotics. These methods include hiding the narcotics in vehicles or carried items, attaching them to one’s body or use of the body as a container. Aviscera case was received by Chemical Examiner Laboratory (CEL) in July, 2015 with history of suspected drug overdose along with two capsules (one intact and one ruptured). This was a case of body packer which was clarified from the copy of postmortem report (PMR) sent by autopsy surgeon along with various exhibits. We are writing this case because this is the only reported body packer syndrome in which viscera was analyzed by CEL.